ANALISIS KESELAMATAN DAN KESEHATAN KERJA TERHADAP JOB SAFETY ANALYSIS DAN STANDAR OPERATIONAL PROCEDURE PADA TAMBANG BATUBARA BAWAH TANAH CV. TAHITI COAL, SANGKAR PUYUH, KECAMATAN TALAWI, KOTA SAWAHLUNTO, PROVINSI SUMATERA BARAT - Rizky Dhanni Fajri; Tri Gamela Saldy (Journals Mining Engineering : Bina Tambang, 2021)
CV. Tahiti Coal is an underground coal mining company located in Sangkar Puyuh, Talawi District, Sawahlunto, West Sumatra. CV. Tahiti Coal has implemented occupational safety and health (K3) in mining activities, but the implementation is still not optimal. This is due to the non-optimal use of personal protective equipment (PPE), some workers who do not comply with company regulations, the occurrence of work accidents, the need for making JSA and the required SOPs. The K3 analysis that has been applied uses a questionnaire with a knowledge value of 61.66, an attitude value of 63.37, and an action value of 59.9. Where the overall results of the questionnaire with a value of 60.31. If the value is adjusted based on the Likert scale, it is in a good range (46-60). JSA and SOP were made on jack hammer operation, lorry operation, and hauling process activities.